Management of the sucking pest complex coconut eriophyid mite coreid bug and button mealy bug infesting coconut bunches - Priya Mohan (Department of Agricultural Entomology, College of Agriculture, 2001)
A study was conducted at the College of Agriculture, Vellayani from April 2000 to July 2001 to investigate the nature and extent of damage caused by the sucking pest complex, coconut eriophyid mite (CEM), coconut coreid bug (CCB) and coconut button mealy bugs (CB M) infesting coconut bunches and to devise suitable chemical and biological management measures against them. CEM, CCB and CBM attack coconut bunches singly or in combinations, the combined attack of CEM and CCB being the most predominant. The coconut palms suffered heavy loss due to the combined infestation of" these pests by way of premature nut fall , varying degrees of damage in retained nuts, distortion and stunting of nuts and formation of barren nuts. An annual premature nutfall of 101.5 nuts palm" was observed due to sucking pest infestation, the share of nut fall due to CEM, CCB and the combined infestation of CEM and CCB being 35.96 per cent, 36.45 per cent and 27.59 per cent respectively. Maximum nutfall was observed in November. 5.81 nuts bunch" palm" were rendered barren or stunted due to infestation of button mealy bugs, singly or in combination with other pests. The infestation of CEM in retained nuts was more or less uniform all through the year whereas CCB showed wide fluctuation with maximum infestation in bunches that opened in November. A new scoring technique was developed, based on surface damage by the pests to assess the loss incurred due to combined infestation of CCB and CEM. Significant negative correlation was observed between surface damage